The Research of Literary Criticism (Materialism in The Great Gatsby Novel by Fitzgerald) - Jaftiyatur Rohaniyah (Universitas Islam Madura, 2016)
The material as the life’s necessities of human changes into prestige of the human himself. Material is no longer interpreted as the life’s necessities but it changes into money. It becomes the symbol of success and happiness. This shift process certainly brings a lot of change to the human nature. Material which at the beginning is considered as the life necessities turns into human obsession to reach the happiness. In the literary criticism, materialism is one of approach to analyze the values in the literary works. Its used by Fitzgerald to view the complexity of the story in the ‘Great Gatsby’ Novel, but unfortunately the fact, its ironic because material satisfaction is only empty happiness as reflected in this paper.